2020
DOI: 10.1002/fsn3.1473
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion and nixtamalization conditions influence the magnitude of change in the nutrients and bioactive components of cereals and legumes

Abstract: Cereal and legume diets make up the bulk of caloric sources for a majority of households in the developing world. They contain macro-and micronutrients as well as phytochemicals embedded as one matrix. Some phytochemicals are antinutritional factors which can bind nutrients thereby hindering their bioavailability. While there are other methods that can be used to enhance nutrient utilization from such foods, we summarize how food processing methods such as extrusion and nixtamalization are employed to break th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 87 publications
(166 reference statements)
0
44
0
4
Order By: Relevance
“…They showed that nuts, beans, insects, fish or protein powders (from pea, soy or whey) provided the highest efficiency with the least EnvI, while beef, cheese, and some processed refined grains (such as rice or egg pasta) were the least efficient and had the highest EnvI. However, the list of products and serving sizes analyzed in the current study was not extensive enough (due to the lack of availability of some data) and we did not analyze the combination of different protein sources (animal with plant-based combinations) or culinary techniques that could complement or increase amino acid availability of plant-based sources [ 88 , 89 , 90 ]. In athletes, only limited research has integrated DIAAS of plant-based diets.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that nuts, beans, insects, fish or protein powders (from pea, soy or whey) provided the highest efficiency with the least EnvI, while beef, cheese, and some processed refined grains (such as rice or egg pasta) were the least efficient and had the highest EnvI. However, the list of products and serving sizes analyzed in the current study was not extensive enough (due to the lack of availability of some data) and we did not analyze the combination of different protein sources (animal with plant-based combinations) or culinary techniques that could complement or increase amino acid availability of plant-based sources [ 88 , 89 , 90 ]. In athletes, only limited research has integrated DIAAS of plant-based diets.…”
Section: Discussionmentioning
confidence: 99%
“…A 95% decrease has been reported by extruding beans at temperatures comprised between 120 and 150 • C, with a total inactivation at 180 • C [60]. Significant destruction of trypsin inhibitors can be achieved by extrusion at elevated temperatures or by increasing residence time when extrusion is done at lower temperatures [78]. Lectins bind sugar branches of the epithelial surface proteins of the digestive tract, resulting in a disruption of the barrier function, which hampers the absorption of nutrients in the gut [79].…”
Section: Effect On Anti-nutritional Factors and Functional Compoundsmentioning
confidence: 99%
“…This is of particular importance in geographic areas where is needed to relief malnutrition. However, the cost of purchasing and operating the extruders may be not affordable in developing countries [78]. A solution to this situation may be the application of simple, autogenic single-screw extruders, which are still available on the markets.…”
Section: Effect On Anti-nutritional Factors and Functional Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that processing of pulses or pulse-based mixtures can also increase, reduce/inactivate or produce minor changes in the content of other non-nutritive components such as protease inhibitors, galactosides, lectins, phenols or phytates [ 1 , 5 , 12 , 13 , 14 , 15 , 16 ]. Although the beneficial effects of these components mainly depend on their bioavailability in the gut, and since there currently is not a recommended daily intake of bioactive compounds, it would be of great interest to know the level of each bioactive compound to be consumed in the processed foods, because processing can disrupt the food matrix, making phytochemicals more or less bioaccessible [ 17 ].…”
Section: Introductionmentioning
confidence: 99%